2019
DOI: 10.1371/journal.pone.0223474
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of anti-Toxoplasma gondii antibodies in wild boars (Sus scrofa), hunting dogs, and hunters of Brazil

Abstract: Seroprevalence of Toxoplasma gondii has been extensively studied in wild boars worldwide due to the emerging risk for human infection through meat consumption. However, this is the first study that reports toxoplasmosis seroprevalence in wild boars, wild boar hunters and their hunting dogs. The aim of the present study was to evaluate the seroprevalence of anti-T. gondii antibodies in the complex wild boars, hunting dogs and hunters, and to determine the risk factors associated with seropositivity in southern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 42 publications
(60 reference statements)
2
17
0
Order By: Relevance
“…A higher seroprevalence of T. gondii than N. caninum, as observed in this study, was also reported by AyINMODE et al (2016) andMACHACOVA et al (2016), demonstrating a greater environmental spread of these parasites in rural areas. Besides, there was no difference between T. gondii and N. caninum regarding gender, as same reported in previous studies in hunting (AyINMODE et al, 2016, CANO-TERRIZA et al, 2016, COLLANTES-FERNANDEZ et al, 2008, MACHACOVA et al, 2016, MACHADO et al, 2019 and pet dogs (CABRAL et al, 1998, DA PAZ et al, 2019, GARCIA et al, 1999 showing that there is no higher predisposition to seroconversion -------------------------------------------------------------------------Toxoplasma gondii-----------------------------------------------------------------…”
Section: Accordingsupporting
confidence: 85%
See 2 more Smart Citations
“…A higher seroprevalence of T. gondii than N. caninum, as observed in this study, was also reported by AyINMODE et al (2016) andMACHACOVA et al (2016), demonstrating a greater environmental spread of these parasites in rural areas. Besides, there was no difference between T. gondii and N. caninum regarding gender, as same reported in previous studies in hunting (AyINMODE et al, 2016, CANO-TERRIZA et al, 2016, COLLANTES-FERNANDEZ et al, 2008, MACHACOVA et al, 2016, MACHADO et al, 2019 and pet dogs (CABRAL et al, 1998, DA PAZ et al, 2019, GARCIA et al, 1999 showing that there is no higher predisposition to seroconversion -------------------------------------------------------------------------Toxoplasma gondii-----------------------------------------------------------------…”
Section: Accordingsupporting
confidence: 85%
“…There also was no statistical difference in the seroprevalence of T. gondii and N. caninum between the age. Previous studies have reported a higher seroprevalence in older dogs, which is attributed to the significant cumulative exposure of dogs to this agent in the environment (CANO-TERRIZA et al, 2016, MACHACOVA et al, 2016, MACHADO et al, 2019. Only one dog had antibodies against Leishmania spp., which demonstrates the low prevalence of leishmaniasis in the rural area of Campo Grande.…”
Section: ------------------------------------------------------------mentioning
confidence: 91%
See 1 more Smart Citation
“…Dogs have also been proposed as toxoplasmosis sentinels for human infection, mostly due to sharing inhouse spaces and related exposure to food and water sources [ 6 , 7 , 8 ]. The overall seropositivity in dogs in this study (23.3%) was lower than the 40.8% in Bahia State, northeastern Brazil [ 48 ], 40.0% [ 10 ] and the 25.4% in Sao Paulo State, southeastern Brazil [ 8 ], the 36.5% in Bahia State, northeastern Brazil [ 49 ], the 34% in Rio de Janeiro State, southeastern Brazil [ 50 ], and the 32.7% in southern and central-western Brazil [ 28 ]; only higher than the 16.3% [ 27 ] and the 7.95% in the same Parana State, southern Brazil [ 9 ]. In addition, the observed seropositivity herein was lower than the 72.7% in Cuba [ 7 ] and higher than the 18.6% [ 51 ] and the 21.6% in China [ 52 ].…”
Section: Discussionmentioning
confidence: 86%
“…To the authors’ knowledge, this was the first concomitant study on the occurrence of T. gondii antibodies in owners and their dogs living on islands and seashore mainland areas. The overall owner seropositivity in this study of the 18.0% was lower than most previous serosurveys, including the 49.8% in San Carlos Island, Venezuela [ 25 ] and all other Brazilian studies, with the 68.7% in the Pará State, northern Brazil [ 26 ], the 50.4% in the Fernando de Noronha Island, far northeastern Brazil [ 3 ], the 41.5% [ 27 ] and the 36.8% [ 9 ] in the same Parana State, southern Brazil, and average of the 32.7% in southern and central-western Brazil [ 28 ]. Seropositivity in the present study was higher than the 12.4% in Panama [ 29 ] and the 5.1% in provinces of China [ 30 ].…”
Section: Discussionmentioning
confidence: 99%